2007
DOI: 10.1136/bjsm.2007.037929
|View full text |Cite
|
Sign up to set email alerts
|

Work And Peak Torque During Eccentric Exercise Do Not Predict Changes In Markers Of Muscle Damage

Abstract: These results suggest the large inter-subject variability in responses to eccentric exercise is not associated with work performed or torque generated during eccentric exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
4
30
3
1
Order By: Relevance
“…It has been established that decreases in maximal voluntary isometric and isokinetic contraction torque, increases in plasma CK activity and muscle soreness, and a rightward shift in the muscle length-tension relationship are evident for an extended period of time (i.e., 1-7 days after exercise) (Philippou et al 2004;Prasartwuth et al 2006;Chen et al 2007;Hubal et al 2007;Chapman et al 2008;Kamandulis et al 2010). In the present study, for the subjects of all groups the following indirect markers of muscle damage emerged within 48 h of eccentric exercise: muscle soreness; Note: Values are means (±SD).…”
Section: Causes Of Depressed Neuromuscular Function After Eccentric Ementioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that decreases in maximal voluntary isometric and isokinetic contraction torque, increases in plasma CK activity and muscle soreness, and a rightward shift in the muscle length-tension relationship are evident for an extended period of time (i.e., 1-7 days after exercise) (Philippou et al 2004;Prasartwuth et al 2006;Chen et al 2007;Hubal et al 2007;Chapman et al 2008;Kamandulis et al 2010). In the present study, for the subjects of all groups the following indirect markers of muscle damage emerged within 48 h of eccentric exercise: muscle soreness; Note: Values are means (±SD).…”
Section: Causes Of Depressed Neuromuscular Function After Eccentric Ementioning
confidence: 99%
“…It is well established that unaccustomed eccentric exercise brings on the symptoms of exercise-induced muscle damage (Warren et al 1999;Fridén and Lieber 2001;Clarkson and Hubal 2002;Byrne et al 2004). These include the prolonged impairment of muscle function (ranging from 30-60 min to 2-4 weeks after exercise) (Warren et al 1999;Byrne et al 2004;Hubal et al 2007;Black and McCully 2008;Chapman et al 2008;Skurvydas et al 2006Skurvydas et al , 2008; the disruption of the intracellular muscle structure, sarcolemma, and extracellular matrix (Fridén and Lieber 2001;Clarkson and Hubal 2002); remodeling of myofiber structure (Yu et al 2002); leakage from injured muscle fibers and delayed-onset muscle soreness, stiffness, and swelling (Clarkson and Hubal 2002); and induces a rightward shift in the optimum joint angle for voluntary isometric strength (Proske and Morgan 2001;McHugh and Tetro 2003;Philippou et al 2004;Chen et al 2007) and concentric strength (Yeung and Yeung 2008;. Muscle-damaging exercise also impairs voluntary activation of muscle (Prasartwuth et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We did not control for TW, as we wanted to investigate the effect of the same number of contractions and velocity, modulating only total ROM. Although the difference in TW could have an impact on the results, it may not be large, as it was demonstrated that TW performed at the ECC did not correlate well with changes in any indirect muscle damage markers [20]. Chapman et al [20] suggest that high variability in the changes in common markers of muscle damage after eccentric exercise could be explained by the variability in TW produced in the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Interessantemente, essa diferença no déficit de força após o protocolo (aproximadamente 54% maior para o grupo AR comparado ao grupo BR) não foi dependente dos níveis de contração voluntária máxima pré, do trabalho total ou torque excêntrico realizados no EE (sem diferenças entre os grupos), corroborando com sugestões prévias 16 . É preciso notar que o pico de queda da capacidade de geração de força que foi utilizado em nosso estudo para a divisão em clusters levou em consideração apenas os valores de 24h-96h após o protocolo, uma vez que a medida imediatamente após o EE pode ter grande interferência da fadiga induzida pelo protocolo e não somente efeito do dano muscular na capacidade de geração de força 17 .…”
Section: Discussionunclassified